Hak Kekayaan Intelektual sebagai Kepemilikan Tak Berwujud dalam Persfektif Fikih Muamalah Kontemporer - Nurlatifah; Muhammad Aldi Akbar; Erwan Setyanor (PT. Pustaka Andil Lestari, 2025)
Intellectual Property (IP) is a manifestation of human intellectual ability that holds moral, economic, and social value. This study examines the definition, scope, and protection of IP from the perspective of contemporary Islamic commercial jurisprudence (fiqh muamalah) and Islamic law, while also reviewing national and global issues concerning IP violations. At the national level, the widespread piracy of books, software, and films in Indonesia reflects low public awareness of copyright, contradicting the Islamic principles of justice and trustworthiness. At the global level, the COVID-19 pandemic raised ethical dilemmas regarding vaccine patents, requiring a balance between IP protection and public access to healthcare. The Islamic perspective emphasizes that IP protection is important but not absolute; in emergency situations or for the public benefit, flexibility is permitted to ensure hifẓ al-nafs (protection of life) and maslahah ‘āmmah. The study concludes that IP should be respected as an asset of both economic and moral value, while its implementation must consider social, economic, and Shariah contexts.